1990
DOI: 10.1002/jnr.490270419
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter changes in alzheimer's disease: Implications to diagnostics and therapy

Abstract: Changes in the cholinergic, serotonergic, noradrenergic, dopaminergic, GABAergic and somatostatinergic neurons were investigated to determine their roles in Alzheimer's disease (AD). Markers for these systems were analyzed in postmortem brain samples from 20 patients with AD and 14 controls. In the CSF study, markers for the cholinergic neurons (choline esterase, ChE) and for the somatostatinergic neurons (somatostatin-like immunoreactivity, SLI) were assayed for 93 and 75 probable AD patients and 29 and 19 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
0
2

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(116 citation statements)
references
References 52 publications
7
107
0
2
Order By: Relevance
“…Photolabeling of the 42-kDa protein was completely protected by the addition of 400 p.M ATP, whereas the 66-and 28-kDa proteins were only partially protected (lanes [13][14][15][16]. This indicated that the 42-kDa binding protein is very specific for ATP, as was confirmed later (see Fig.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Photolabeling of the 42-kDa protein was completely protected by the addition of 400 p.M ATP, whereas the 66-and 28-kDa proteins were only partially protected (lanes [13][14][15][16]. This indicated that the 42-kDa binding protein is very specific for ATP, as was confirmed later (see Fig.…”
Section: Resultssupporting
confidence: 73%
“…[y32P]2N3ATP (specific activity, [5][6][7][8][9][10][11][12][13][14] mCi/,tmol) was then prepared and purified as described for ['t-32P]8N3ATP. Protein molecular size standards were from Bio-Rad.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-mortem and CSF studies have shown deficits in cholinergic, serotonergic, dopaminergic, somatostatinergic, noradrenergic, and glutaminergic neurotransmitters. 19 Inflammatory and oxidative alterations are also thought to contribute to neural dysfunction and neural death. 20,21 These and various other pathogenic mechanisms, such as hyper tension and insulin resistance, further contribute to compromised cerebral blood flow, regional decreases in glucose metabolism, white-matter hyperintensities, and small strokes.…”
Section: Brain Alterations In Age-related Cognitive Declinementioning
confidence: 99%
“…Pharmacological approaches to providing a palliative treatment for AD have thus been aimed at enhancing transmission at the cholinergic synapses remaining in this region (Reinikainen et al, 1990; Kumar & Calache, 1991). Agents affecting the cholinergic system which have been examined with varying success include arecoline (Christie, 1982), bethanechol (Penn et al, 1988;Read et al, 1990), physostigmine (Muramoto et al, 1984;Harrell et al, 1990), and tetrahydroaminoacridine (THA) (Summers et al, 1986;Molloy et al, 1991).…”
Section: Introductionmentioning
confidence: 99%